2004
DOI: 10.1016/j.jvs.2003.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of outcomes after surgical management of venous disease incorporating subfascial endoscopic perforator surgery

Abstract: Our results suggest that surgical management of venous ulcer including SEPS, with or without saphenous ablation, leads to an 88% chance of ulcer healing and a 13% chance of ulcer recurrence over the short term. Randomized controlled trials are needed to discern the contributions of compression therapy, superficial venous surgery, and SEPS in the treatment of venous ulcer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 37 publications
(151 reference statements)
3
76
0
2
Order By: Relevance
“…16) For patients with severe CVI and active venous ulcers (C6), an intervention that improves healing and prevents recurrence has the potential to improve quality of life and reverse disability associated with this condition. 16) The healing and recurrence outcomes after SEPS are, reportedly, much better than those in most trials of conservative VAC therapy combined with compression banding, which was started on the 10th postoperative day and was continued for 4 weeks. The patient underwent skin grafting between d and e. therapies, even though the patient population in these surgical studies generally had severe venous disease and inadequate response to conservative therapies.…”
Section: Casementioning
confidence: 99%
“…16) For patients with severe CVI and active venous ulcers (C6), an intervention that improves healing and prevents recurrence has the potential to improve quality of life and reverse disability associated with this condition. 16) The healing and recurrence outcomes after SEPS are, reportedly, much better than those in most trials of conservative VAC therapy combined with compression banding, which was started on the 10th postoperative day and was continued for 4 weeks. The patient underwent skin grafting between d and e. therapies, even though the patient population in these surgical studies generally had severe venous disease and inadequate response to conservative therapies.…”
Section: Casementioning
confidence: 99%
“…In the treatment of venous ulcers that are located above the ankle, it is recommended to include treatment of incompetent PV in combination with SVI therapy [19,25]. In patients with a combination of SVI and PVI, routine PVI treatment is recommended by some authors, along with SVI treatment because of the risk of recurrence [6,[25][26][27]. Incompetent PVs can be treated with surgical ligation, US-guided sclerotherapy, endovascular thermal, laser therapy, or radiofrequency ablation [24].…”
Section: Discussionmentioning
confidence: 99%
“…It has largely replaced the more invasive Linton procedure, which involved open surgical visualization and ligation of incompetent perforator veins. A recent systematic review of 20 studies using SEPS showed an overall venous ulcer healing rate of 88% at 1 year, with the majority being improved within 60 days [49]. Standard procedure Most commonly, SEPS is performed using a two-port technique using standard laparoscopic equipment.…”
Section: Subfascial Endoscopic Perforator Surgerymentioning
confidence: 99%
“…Contraindications Patients with severe peripheral arterial disease have a relative contraindication to this procedure due to poor wound healing [51]. Complications Early surgical complications include wound infection, hematoma, neuralgia, and rare deep vein thrombosis [49]. Up to 6% of perforators may be missed on initial surgery [49].…”
Section: Subfascial Endoscopic Perforator Surgerymentioning
confidence: 99%
See 1 more Smart Citation